1996
DOI: 10.1007/bf03162055
|View full text |Cite
|
Sign up to set email alerts
|

The universality of the electron spin relaxation in C60 mono radical anion salts: EPR studies of the model system [P(C6H5)4]2C60X

Abstract: The C 60 radical anion salts [P(C 6Hs)4hC60X (X = Cl, Br, I) are grown via electrocrystallization and used as a model system to study the electron spin and nuclear spin dynamics as well as the molecular dynamics of C 60 mono anions in the solid state, which obey universal laws. It is shown that [P(C 6Hs)4hC60X is an exception among the fullerides, since the temperature dependence of the JT distortion, predicted for ionic C 60 , can be deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…This is readily ascribed to dynamic averaging of ellipsoidal structures to give effective icosahedral symmetry (so-called pseudorotation). 116,117,347,352,353 It finds a counterpart in the dynamic collapse of anisotropy in the EPR spectrum of triplet state C 60 which occurs over a similar temperature regime. 354 Phase memory relaxation rates acquired by electron spin-echo techniques are faster in the high-field tail of the C 60 -spectrum than in the central portion.…”
Section: Anisotropymentioning
confidence: 97%
See 1 more Smart Citation
“…This is readily ascribed to dynamic averaging of ellipsoidal structures to give effective icosahedral symmetry (so-called pseudorotation). 116,117,347,352,353 It finds a counterpart in the dynamic collapse of anisotropy in the EPR spectrum of triplet state C 60 which occurs over a similar temperature regime. 354 Phase memory relaxation rates acquired by electron spin-echo techniques are faster in the high-field tail of the C 60 -spectrum than in the central portion.…”
Section: Anisotropymentioning
confidence: 97%
“…352 Recently, single-crystal EPR spectra have been obtained for a C 60 -salt. 352,353 The observation of two precisely defined g values gives more insight into the nature of the Jahn-Teller-distorted ground state in this environment. The rationalization of the results requires a molecular symmetry of C 2h or lower.…”
Section: Anisotropymentioning
confidence: 99%
“…[24][25][26][27][28][29] A recent CW EPR study of crystalline ͑Ph 4 P͒ 2 IC 60 reports a transition from a dynamic to static JTE near 140 K, manifest in g-factor splitting and bandwidth narrowing at low temperature. 6,11,30 Pulsed EPR measurements on the chloride-containing salt show Orbachtype spin-lattice relaxations, consistent with JT vibronic excitations. 31 ͑Ph 4 P͒ 2 IC 60 can be compared to other solid-state fullerene materials with regards to the charge and symmetry states of the ball and the degree of separation between balls.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, we supplement the vibrational studies reported to date 8,9,12,16 and complement the previous EPR temperature dependence work. 6,11,31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation